Pendekatan Deep Learning dalam Pembelajaran IPAS: Meningkatkan Pemahaman Konsep Peserta Didik Madrasah Ibtidaiyah Pada Materi Lingkungan Hidup - Muhammad Irfanullah Hakim; Damar Septian (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Low students' conceptual understanding in Integrated Science and Social Studies (IPAS) is one of the challenges in implementing the Merdeka Curriculum, particularly in the topic Becoming Environmental Heroes. This study aimed to describe the results of implementing the deep learning approach on students' conceptual understanding of IPAS and to examine the effect of this approach on students' conceptual understanding. This research employed a quantitative approach using a quasi-experimental design. The sample consisted of 89 fourth-grade students of MI Tahfidzul Qur’an Raudlatul Falah Bermi, including 45 students in the experimental class and 44 students in the control class. Data were collected through essay tests and analyzed using descriptive and inferential statistics. The findings showed that the experimental class achieved a mean conceptual understanding score of 71.20, which was categorized as good. The Mann–Whitney U Test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the experimental and control groups. Therefore, the deep learning approach has a significant effect on students' conceptual understanding of IPAS in the topic Becoming Environmental Heroes.